Assessing the Potential of Using the Langdon 5D(5B) Substitution Line for the Introgression of Aegilops tauschii Into Durum Wheat - Othmeni, Manel; Grewal, Surbhi; Walker, Jack; Yang, Cai-yun; King, Ian P.; King, Julie (Frontiers in Plant Science, 2022)
Aegilops tauschii, the D-genome donor of hexaploid wheat, provides a source of genetic variation that could be used for tetraploid (durum) wheat improvement. In addition to the genes for wheat quality on the D-genome, which differentiate between bread and durum wheats in terms of end-use properties, genes coding for resistances to biotic and abiotic stresses are also present on the D-genome which would be useful in durum wheat. The introgression of Ae. tauschii into durum wheat, however, requires cytogenetic manipulation to induce homoeologous chromosome pairing to promote recombination. For this purpose, the introgression of Ae. tauschii into durum wheat was performed through a bridge cross of the wild species to the Langdon 5D(5B) disomic substitution line that lacks the Ph1 locus present on chromosome 5B, followed by a cross of the F1 to the durum wheat cultivar Om Rabi 5. Subsequent generations were self-fertilized, and these were screened for D-genome introgressions using (i) D-genome-specific Kompetitive Allele-Specific PCR (KASP) markers and (ii) KASP markers polymorphic between the 5D chromosomes of wheat, present in the Langdon 5D(5B) substitution line, and of Ae. tauschii. Homozygous introgression lines were confirmed using genomic and fluorescence in situ hybridization. The results showed that the use of the Langdon 5D(5B) disomic substitution line did not promote D-genome introgression across all linkage groups with only a limited success in the introgression of Ae. tauschii 5D segments into durum wheat.